GE_GERICHTE P/23758/2014 vom 6. Februar 2018 - GE Cour de justice (2018)
ABUS DE CONFIANCE; INFRACTIONS CONTRE LE PATRIMOINE ; PLAIGNANT ; PARTIE CIVILE ; PÉREMPTION ; DOMMAGE | CP.138.al1.ch2; CP.70.al1; CP.73.al1.letc; CPP.122; CPP.123.al1; CPP.123.al2; CPP.122.al4; CPP.126.al1.leta; CPP.126.al2.letb; LaCP.3.lety